1992
DOI: 10.1007/bf03008779
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled lumbar epidural fentanyl compared with patient-controlled intravenous fentanyl for post-thoracotomy pain

Abstract: Thirty-four patients undergoing thoracotomy were entered into a randomized, double-blind, placebo-controlled study to compare the effects of patient-controlled, lumbar epidural (PCA-E) fentanyl with patient-controlled intravenous (PCA-iv) Trente-quatre patients devant subir une thoracotomie ont dtd ~valu~s dans le cadre d'une Etude h double insu, au hasard et avec contrOles placebo afin de comparer les effets du fentanyl Epidural contr~le par le patient (PCA-E) au fentanyl intraveineux contr61E par le patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 12 publications
1
21
0
3
Order By: Relevance
“…3,11,15,21 Some investigators found that the plasma concentration of fentanyl was much lower after epidural injection than after intravenous administration. 12,16 In the present study, only two patients in group 1 and one patient in group 2 presented a fentanyl concentration of 0.63 ng/ml during the period analyzed.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…3,11,15,21 Some investigators found that the plasma concentration of fentanyl was much lower after epidural injection than after intravenous administration. 12,16 In the present study, only two patients in group 1 and one patient in group 2 presented a fentanyl concentration of 0.63 ng/ml during the period analyzed.…”
Section: Discussionmentioning
confidence: 48%
“…Several investigators [7][8][9][10][11][12][13][14][15][16][17][18][19][20] have evaluated the mechanism of action of fentanyl administered epidurally. Although many studies 3,9-12,15,17 have concluded that the mechanism of action is associated with systemic absorption of the opioid into the circulation, followed by a supraspinal effect, many investigators continue to use fentanyl as a continuous infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers compared epidural route and the above mentioned method and noted that there exists no diŠerence in e‹ciency, but former route is more advantageous for additional doses and that both methods are superior to intermittent dosing. 14) It was reported that intravenous analgesia with PCA after CABG operations is superior to conventional nurse determined analgesic administration as signiˆcantly less postoperative atelectasis with the former method. 9) In previous researches, it had been shown that patients in PCA group after CABG procedures had more rapidly decreasing VAS scores than those in conventional analgesia group.…”
Section: Discussionmentioning
confidence: 99%
“…Is-E~ Recent studies have questioned whether the analgesic efficacy of epidural fentanyl is secondary to systemic absorption and recirculation to the central nervous system through the blood-brain bartier, 12,15,16,23 or is mediated by a direct spinal mechanism. 25 If the former were the case, then there may be no advantage to the epidural route.…”
Section: Cette Dtude Randomisde Et ?T Double Aveugle Compare Pendant mentioning
confidence: 99%